The Transformation of Hadhanah in the Digital Era: Islamic Parenting Strategies with Technology - ani, sulhani; Paujan Azim; M Azik; Nu Sopyah; Badriyah (NALAR FIQH: Jurnal Hukum Islam, 2024)
The concept of hadhanah, rooted in Islamic parenting principles, encompasses physical, moral, and spiritual care for children. In the digital era, parents face unique challenges, particularly in semi-urban settings like Mendalo Indah, where rapid technological adoption influences traditional childcare practices. Despite the growing discourse on digital parenting, limited studies explore how Islamic values integrate with technology in such contexts. This qualitative research employs a phenomenological approach, combining participatory observation and in-depth interviews with parents, educators, and religious leaders in Mendalo Indah. The findings reveal that while 70% of parents utilize Islamic apps, only 25% actively supervise children's internet use, highlighting a significant gap between the idealization of Islamic parenting and its practical application in the digital age. Furthermore, parents struggle with balancing work and parenting responsibilities, often relying on unsupervised technology that risks moral degradation. The study emphasizes the importance of Islamic digital literacy, including strategies for content filtering, productive screen time, and dialogic engagement, as well as community-based initiatives involving ulama and local leaders. These findings underscore the need for a holistic parenting paradigm that integrates spiritual values with modern technology, positioning parents as navigators of both religious and digital ecosystems. This research provides actionable insights for creating adaptive, value-based Islamic parenting strategies that respond to contemporary challenges while preserving traditional principles.